Firearms and Injuries during Home Robberies in Mexico, 2010–2017 - Weigend Vargas, Eugenio (Trends in organized crime, 2022)
According to data from Mexico’s National Crime Victimization and Public Security Surveys (ENVIPE), from 2010 through 2017, home robberies involving an interaction between a victim and an aggressor occurred every two minutes and resulted in more than 257,000 injuries. The objective of this study is to explore whether victims of home robberies in Mexico are more likely to report an injury if perpetrators are armed with a gun. This analysis compiles data from ENVIPE and runs a binary logistic regression. In contrast to literature on robberies in the United States and studies on street robberies in Mexico, results show that when perpetrators are armed with guns, victims of home robberies in Mexico are more likely to report an injury, even though these injuries are rarely caused by a gunshot. These discrepancies may be explained by different factors. Unlike in the United States, most gun-related crimes in Mexico are perpetrated by organized criminal groups that obtain firearms through illegal channels. Members of these groups are prepared to engage on physical violence against their victims. Additionally, unlike street robberies, the enclosed setting of home robberies might facilitate the use of physical violence as a strategy to coerce victims and successfully obtain profits without generating public attention. Overall, perpetrators use guns as a tool to exert control and avoid resistance. These findings suggest that policies to address organized crime and halt easy access to guns should be prioritized on Mexico’s national security agenda.